THE USE OF CONTEXTUAL VIDEO TO IMPROVE STUDENTS` LISTENING ABILITY - Mardiya Kamilah (Journal of English and Education, 2013)
The major goals of the study were to investigate the effectiveness of contextual video usage in improving the students’ listening ability and to find out the students’ responses toward the use of contextual video in listening practice related to the students’ English knowledge and the students’ psychology. The study included eight graders of junior high school as the participant that were designed into two groups: experimental class and control class. This study was accomplished by comparing the students’ listening score in experimental class to the students’ listening score in control class using independent t-test and the data were collected use pilot-test, pre-test, post-test and a questionnaire. This study revealed that, on average, the students’ listening score in experimental class that learn through contextual video (M =79.45, SE=1.69, p0.05) is higher than the students’ listening score in control class that learn through conventional method (M=73.21, SE=1.96) with medium effect size (r=0.269). Thus it can be assumed that contextual video is effective in improving students’ listening ability. Furthermore, the result of questionnaire analysis also revealed that the students’ responses toward the use of contextual video in listening practice were positive. Most students stated that contextual video gave more advantages than the disadvantages related to their English knowledge and psychology. The study was concluded that contextual video can be used as an alternative teaching medium for listening practice. For consideration, contextual video can also be used in other topics or even subjects. Keywords:Listening, Listening Ability, Teaching Listening, Contextual Video